CORRELATION BETWEEN GLYCATED HEMOGLOBIN AND LIPID PROFILE STATUS AMONG NEWLY-DIAGNOSED TYPE 2 DIABETICS OF INDIVIDUALS OF THREE ETHNIC GROUPS IN SOKOTO, NIGERIA (Journal of Biomedical Investigation, 2025)
Background: Glycated haemoglobin (HbA1c) has been suggested to be a better predictor for coronary heart disease and strongly associated with atherosclerosis. Changes in lipid profile is linked with severity of diabetes as adjudged by HbA1c. Lipid abnormalities are common in type 2 diabetics, but the pattern may vary between ethnic groups. Aim: The current study was undertaken to explore the association of HbA1c and serum lipid profile parameters in type 2 diabetics among persons of three ethnic groups in Sokoto.Methods: The current study was a cross-sectional case-control study. The Cochran formula was used to determine the number of subjects recruited. Demographic and clinical characteristics were obtained from all the participants. HbA1c and lipid profile parameters were determined using standard laboratory tests. Ranges for TC
Keywords: Type 2 diabetics; Glycated haemoglobin; Lipid profile; Sokoto Ethnic Groups